2020
DOI: 10.3390/su12030995
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Knowledge and Seasonal Calendar Inform Adaptive Savanna Burning in Northern Australia

Abstract: Indigenous fire management is experiencing a resurgence worldwide. Northern Australia is the world leader in Indigenous savanna burning, delivering social, cultural, environmental and economic benefits. In 2016, a greenhouse gas abatement fire program commenced in the savannas of south-eastern Arnhem Land in the Northern Territory, managed by the Indigenous Yugul Mangi rangers. We undertook participatory action research and semi-structured interviews with rangers and Elders during 2016 and 2019 to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 45 publications
1
64
0
1
Order By: Relevance
“…These indicators were defined as predictable, obvious, seasonal events that may or may not be known as culturally significant (e.g. arrival or departure of migratory birds, breeding animals, flowering or fruiting plants similar to 'calendar plants' described in Clarke 2018; see also McKemey et al 2020a). The biocultural seasonal indicators were aligned with fire conditions to provide guidelines for contemporary cultural fire management, and were presented in Winba = Fire, the Banbai Fire and Seasons Calendar (hereafter referred to as Winba = Fire).…”
Section: Bring Togethermentioning
confidence: 99%
See 2 more Smart Citations
“…These indicators were defined as predictable, obvious, seasonal events that may or may not be known as culturally significant (e.g. arrival or departure of migratory birds, breeding animals, flowering or fruiting plants similar to 'calendar plants' described in Clarke 2018; see also McKemey et al 2020a). The biocultural seasonal indicators were aligned with fire conditions to provide guidelines for contemporary cultural fire management, and were presented in Winba = Fire, the Banbai Fire and Seasons Calendar (hereafter referred to as Winba = Fire).…”
Section: Bring Togethermentioning
confidence: 99%
“…Around the world, seasonal calendars have been created to collect and share Indigenous knowledge and to signify the connection between people, Country (ancestral estate) and the annual cycles of seasonal change on Country (James et al 2018). Indigenous seasonal calendars have been used in the monitoring and management of water (Woodward et al 2012), agricultural systems (Adjaye 1987;Jiao et al 2012;Bhagawati et al 2017;Saylor et al 2017;Balehegn et al 2019), climate change (Cochran et al 2016;Chisholm Hatfield et al 2018) and fire regimes (Armatas et al 2016;McKemey et al 2020a), and to guide eco-health decision-making (SantoDomingo et al 2016). In Australia, there are at least 38 documented examples of Indigenous seasonal calendars (see Webb 1997;Hill et al 2004;O'Connor & Prober 2010;Bodkin 2013;Turpin et al 2013;Holmes et al 2017;Clarke 2018;McKemey & Ngoorabul Community 2018;McKemey & Wahlabul Nation 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The practice and potential of indigenous ecological knowledge and natural resource management has been documented [36,39,40]. The use of IK for wild fire management is another example out of several potential applications of IK for sustainability [41]. Lozano et al [42] note that indigenous knowledge has the potential to help students learn " .…”
Section: Indigenous Knowledge and Sustainability Competenciesmentioning
confidence: 99%
“…Most prescient was the explorer Thomas Mitchell (1848, p. 412), who, after various expeditions through what is now central-western New South Wales, famously observed that 'fire, grass, kangaroos, and human inhabitants, seem all dependent on each other for existence in Australia'. Revisiting that record, it is only in recent decades that the magnitude and complexity of Indigenous landscape management and modification have begun to be recognised (Nicholson 1981;Pyne 1991;Bowman 1998), especially that associated with agricultural economies in prehistoric temperate south-eastern and south-western Australia (Hallam In addition to these historical accounts, there is a rich ethnographic record, especially for remote and relatively culturally intact central (Gould 1971;Kimber 1983;Latz 1995;Bird et al 2005;Burrows et al 2006;Bliege Bird et al 2008, 2012 and northern Australia (Thomson 1949;Jones 1975Jones , 1980Crawford 1982;Haynes 1985;Russell-Smith et al 1997, 2003Bowman et al 2001Bowman et al , 2004Vigilante et al 2009), including growing numbers of Indigenous perspectives (Yibarbuk 1998;Yibarbuk et al 2001;Garde et al 2009;McGregor et al 2010;Ansell et al 2020;McKemey et al 2020). By contrast, and despite growing recognition of and interest in Indigenous fire knowledge traditions (e.g.…”
Section: Introductionmentioning
confidence: 99%